A study of Santals as children of nature in the light of Santal folktales - Hembrom, Thadeus (Research Journal in Advanced Humanities, 2022)
South Asian nations are home to the Santal tribe. Even though they are dispersed over several nations, most of the Santal are found in India and Bangladesh. The Santal people describe themselves largely as natural beings. This assertion has found support from some scholars who have analysed the Santal rituals and festivals. However, very few studies have tried to define the identity of the Santals from a literary perspective. Therefore, by examining their folktales, this article aims to demonstrate the idea that the Santal are children of nature. The study was guided by The National Folklore Theory, Cultural Functional Theory, and Theory of Reality. The qualitative research was based on a textual analysis of 27 Santal folktales. The rationale of this paper is that Santal folktales serve as a repository of knowledge about their customs, cultures and identities. From the study findings, it is clear that the Santals live in and through nature. They have such intimate relations with nature as one would have with a parent or sibling. They emulate the simplicity of nature in their lifestyle. Even the spirits they worship and revere are thought to reside in nature. Therefore, the Santal are born from nature and exist in mutually beneficial and shared spaces with other creatures in nature.